The Function of MAPK Cascades in Response to Various Stresses in Horticultural Plants - He, Xiaowen; Wang, Chuanzeng; Wang, Haibo; Li, Linguang; Wang, Chen (Frontiers in Plant Science, 2020)
The mitogen-activated protein kinase (MAPK) cascade is a highly conserved signaling transduction module that transmits extracellular environmental signals into plant cells. Early studies of plant MAPKs focused on their functions in model plants. Based on the results of whole genome sequencing, many MAPKs have been identified in horticultural plants, such as tomato, apple, etc. Recent studies revealed that the MAPK cascade also plays crucial roles in biotic and abiotic stress responses of horticultural plants. In this review, we summarize the composition and classification of MAPK cascades in horticultural plants and the recent research on this cascade in response to abiotic stresses (such as drought, extreme temperature and high salinity) and biotic stresses (such as pathogen infection). In addition, we discuss the most advanced research themes related to plant MAPK cascades, helping to improve research on MAPK cascade functions in horticultural plants.